Pengaruh Pemberian Monosodium Glutamate (MSG) dan Macam Pupuk Terhadap Pertumbuhan Bibit Stek Vanili (Vanilla planifolia Andrews) Varietas Vania 1 Satu Ruas - Sari, Intan Nurpita; Historiawati, Historiawati; Oktasari, Wike (JURNAL VIGOR, 2022)
Propagation of vanilla plants can be done vegetatively by cuttings. The problem faced was the length of root and shoot growth on cuttings which can be accelerated by giving MSG. Fulfillment of nutrient needs to support the growth of cuttings can be provided through fertilization. This study was conducted to determine the effect of MSG application and type of fertilizer on the growth of vanilla cuttings (Vanilla planifolia Andrews) of one segment of the Vania 1 variety. The research was carried out from January to May 2022 at The Santan vanilla plantation, Karang Tengah, Sumberrejo, Mertoyudan, Magelang Regency. The study was arranged in a randomized complete block design (RCBD) with two factors and four replications. The first factor was the concentration of MSG, consisting of four concentrations: 0 ppm, 3000 ppm, 6000 ppm, and 9000 ppm. The second factor was the type of fertilizer, consisting of cow manure and NPK fertilizer. Variables observed included shoot emergence, shoot length, number of leaves, longest root length, number of roots, and percentage of live cuttings. Data were analyzed using Analysis of Variance (ANOVA). The results showed that mid-base cuttings had a higher survival value than shoot cuttings. MSG concentration had no significant effect on all parameters. The type of fertilizer did not significantly affect all parameters. There was no interaction between MSG concentration and the type of fertilizer on all parameters.Keywords: MSG, cow manure, NPK fertilizer, vanilla cuttings, Vania 1.